Exploring Morphological Awareness of EFL Students through a Contrastive Analysis Approach - Novriyani Novriyani; Emilda Oktaviyani; Novita Nurdiana; Bintang Rosada (LinguaScopes: International Journal of Language Education, 2026)
Morphological awareness is widely recognized as a central element of language proficiency, particularly within the field of Second Language Acquistion. The present study aims to examine the level of morphological awareness among English as a Foreign Language (EFL) learners by applying a contrastive analysis framework to explore both the structural similarities and differences between English and Indonesian. To achieve this objective, the study adopts a mixed-method research design, integrating quantitative data obtained from morphological assessments with qualitative insights derived from students’ written outputs. The result demonstrate that although learners possess a foundational understanding of morphemic structures, they encounter significant challenges in the accurate use of inflectional morphemes, particularly in expressing tense and number distinctions. The contrastive analysis further indicated that these difficulties are largely attributable to the absence of inflectional morphology in the Indonesian language system. In addition, the incorporation of contrastive analysis into instructional practices has been shown to substantially improve students’ morphological awareness as well as their grammatical precision. Overall, this study highlights the pedagogical significance of contrastive analysis within EFL settings and advocates for its systematic integration into language instruction in order to promote deeper linguistic awareness and enhance overall learning outcomes.